Churches- Miscellaneous - Grady County Historical Society (Valdosta State University Archives and Special Collection, 1851)
Includes lists of rural churches, minutes from the 25th annual session of the Ochlocknee Primitive Baptist Association, death notice for Elder Asa C. Stephenson, lists of Cairo's Black Churches, obituaries, and newspaper clippings. Churches - Miscellaneous. Grady County Historical Society, Grady County Historical Society - Churches Collection. Valdosta State University Archives and Special Collections.
1 PDF, 21 scanned images
Keywords: Grady County (GA.); Church History; Church records and registers; History- Societies, etc.